Reading and learning to read - Vacca, Jo Anne L. (Pearson, 2009)
Promotes a comprehensive approach to teaching reading and writing with an emphasis on research-based best practices, integrating technology, and accommodating the needs of diverse and struggling learners.--from publisher description.